2014
DOI: 10.1136/bmjopen-2014-005123
|View full text |Cite|
|
Sign up to set email alerts
|

Outcomes after corrective surgery for congenital dextro-transposition of the great arteries using the arterial switch technique: a protocol for a scoping systematic review

Abstract: IntroductionDextro-transposition of the great arteries (d-TGA) is a life-threatening congenital health defect that requires rapid surgery. The most widely used approach is the arterial switch operation (ASO) developed by Jatene in the 1970s. The first set of children who received this intervention are now adults. The objective of this scoping review of the literature was to document the short-term (less than 1 year), medium-term (1–20 years) and long-term (more than 20 years) outcomes in children who underwent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…This review was registered with the International prospective register of systematic reviews (PROSPERO), registration number CRD42014007590 [16]. The methods of this study are published elsewhere [16] but outlined here in brief.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…This review was registered with the International prospective register of systematic reviews (PROSPERO), registration number CRD42014007590 [16]. The methods of this study are published elsewhere [16] but outlined here in brief.…”
Section: Methodsmentioning
confidence: 99%
“…This review was registered with the International prospective register of systematic reviews (PROSPERO), registration number CRD42014007590 [ 16 ]. The methods of this study are published elsewhere [ 16 ] but outlined here in brief. The review is reported according to the Preferred Reporting Items for Systematic reviews and Meta-Analyses extension for Scoping Reviews (PRISMA-ScR) (see Appendix 6 ) [ 17 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The optimal surgical plan for simple TGA is the arterial switch operation (ASO), which is commonly performed shortly after birth to prevent left ventricular (LV) deconditioning. 1 - 3 From a clinical point of view, the early diagnosis of TGA is vital to avoid the involution of the LV, which may contribute to the low cardiac output syndrome and LV failure. Assessments of the impact of the surgical time on early outcomes after the repair of TGA have not led to consensus.…”
Section: Introductionmentioning
confidence: 99%